Ambidestreza organizativa en filiales de sectores intensivos en conocimiento (2020)
In the knowledge society, multinationals and, more specifically, their subsidiaries acquire great importance as a source of competitiveness for the multinational as a whole. From this perspective, this article has a double objective: (1) to define ambidextrous subsidiary, and (2) to explore if subsidiaries are ambidextrous. A quantitative methodology is used on a sample of 102 Spanish subsidiaries of foreign multinationals from knowledge-intensive sectors. Findings show that the subsidiaries analyzed are highly explorers of knowledge. However, despite the coherence between the roles played and their international competitive strategies, not all subsidiaries turned out to be ambidextrous. Only those with an integrated player role and transnational strategies can be considered as such.